2022
DOI: 10.3389/fcell.2022.999024
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s disease: Pathophysiology and dental pulp stem cells therapeutic prospects

Abstract: Alzheimer’s disease (AD) is a destructive neurodegenerative disease with the progressive dysfunction, structural disorders and decreased numbers of neurons in the brain, which leads to long-term memory impairment and cognitive decline. There is a growing consensus that the development of AD has several molecular mechanisms similar to those of other neurodegenerative diseases, including excessive accumulation of misfolded proteins and neurotoxic substances produced by hyperactivated microglia. Nonetheless, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 176 publications
(210 reference statements)
0
6
0
Order By: Relevance
“…Since the most prominent molecular pathology of AD is the neurotoxicity of aggregate Aβ and hyperphosphorylated tau protein, which jointly damage neurons and ultimately lead to cognitive decline, we performed immunofluorescence staining to assess whether hDPSCs had modified their progression. 1 The results revealed that the pathological Aβ aggregation and the expression of phosphorylated Tau protein (AT8) in the hippocampus of hDPSCs-treated AD mice were much lesser than those in AD-PBS mice (Fig. 6c, d ).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Since the most prominent molecular pathology of AD is the neurotoxicity of aggregate Aβ and hyperphosphorylated tau protein, which jointly damage neurons and ultimately lead to cognitive decline, we performed immunofluorescence staining to assess whether hDPSCs had modified their progression. 1 The results revealed that the pathological Aβ aggregation and the expression of phosphorylated Tau protein (AT8) in the hippocampus of hDPSCs-treated AD mice were much lesser than those in AD-PBS mice (Fig. 6c, d ).…”
Section: Resultsmentioning
confidence: 87%
“…Prolonged periods of uncontrolled intracerebral homeostatic imbalances lead to abnormal activation of microglia and chronic neuroinflammation, which can further exacerbate neurodegeneration and cognitive impairment. 1 , 14 To investigate the effects of hDPSCs on microglia abnormal activation pathology, we induced BV2 cells with bacterial lipopolysaccharide (LPS) stimulation, which is considered the gold standard for microglia activation. 15 BV2 cells were challenged with different conditions of LPS to determine the best induced effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DPSCs have demonstrated clinical potential not only in dentistry but also in the treatment of various diseases, including craniofacial bone defects, muscle regeneration, myocardial infarction, Alzheimer's disease, nervous system injuries, Parkinson's disease, stress urinary incontinence, osteoarthritis and liver diseases. [16][17][18][19][20][21][22][23][24] This study aimed to investigate whether co-administration of DPSCs and human umbilical vein endothelial cells (HUVECs) could enhance the therapeutic effects of stem cells for critical hindlimb ischemia, compared to the effects of either DPSCs or HUVECs alone. The combination therapy of DPSCs and HUVECs resulted in significantly higher blood flow and reduced ischemic damage compared to the individual administration of DPSCs or HUVECs.…”
Section: Introductionmentioning
confidence: 99%
“…Due to DPSCs' multidirectional differentiation potential and easy accessibility, their application in bone tissue engineering is currently under extensive exploration. DPSCs have demonstrated clinical potential not only in dentistry but also in the treatment of various diseases, including craniofacial bone defects, muscle regeneration, myocardial infarction, Alzheimer's disease, nervous system injuries, Parkinson's disease, stress urinary incontinence, osteoarthritis and liver diseases 16–24 …”
Section: Introductionmentioning
confidence: 99%